Desain dan Implementasi Sistem E-Commerce BUMDes Berbasis Web untuk Peningkatan Pelayanan Pelanggan - Dwi Puspita Anggraeni (Pusat Riset dan Inovasi Nasional, 2022)
Village-Owned Enterprises (BUMDes) management has a strategic role in strengthening the local economy, but Toko Sejahtera still faces obstacles related to stock management, transaction recording, and customer service. The Microsoft Excel-based recording system is considered less effective in reflecting real-time stock of goods, so there is often uncertainty in the availability of goods which causes customer dissatisfaction. This research aims to design and implement a web-based e-commerce system at Toko Sejahtera to overcome these obstacles, by providing a platform that allows customers to check stock items before ordering, as well as update transactions and stock automatically. The system was designed using UML approach with various diagrams, such as use case, class, activity, and sequence to ensure a comprehensive understanding of the system. Testing is done through Black Box Testing to ensure the system functions as expected. The results show that this system can improve operational efficiency, service quality, and customer experience by providing online transaction features, real-time sales reports, and COD payment options.